An Experimental Validation of Simulated Coolant Nozzles and Their Orientation in a Grinding Process - Singh, Mandeep (My University, 2010)
The present study has been done to study the effect of different input parameters on the desired responses in the grinding process. A computational fluid simulation (using ANSYS CFX) approach is being adapted to find the flow behaviour of air around the rotating grinding wheel. Also finding the peak pressure, pressure drop region and the swirl direction, nozzle location can be found out so that the flow coming out of the nozzle can be send to the exact cutting region. Flow behaviour for six different kinds of nozzles has been studied at same boundary conditions to find the best suited nozzle. Also the effect of rotation of grinding wheel and work-piece has been simulated. Partial factorial technique has been used for the design of experiments. The effects of nozzle type, grinding wheel speed, work-piece speed, nozzle tip distance and nozzle angle have been evaluated on the surface roughness, dimensional control and microhardness. The effect of all the input parameters on the output responses have been analyzed using the analysis of variance (ANOVA). The effect of variation in input parameters has been studied on the output responses. Plots of significant factors and S/N ratio have been used to determine the best relationship between the response and the model parameters.
M.E.
Keywords: Grinding, ANSYS, Nozzle, grinding wheel, work piece speed, nozzle tip distance, nozzle angle, surface roughness, dimensional control, microhardness, Taguchi design, ANOVA